KAJIAN SIX SIGMA DALAM PENGENDALIAN KUALITAS PADA BAGIAN PENGECEKAN PRODUK DVD PLAYERS PT X - Nailatis Shofia; Mustafid Mustafid; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Increasingly rapid development period, many industry sectors are growing and developing in Indonesia. Quality basic consumer decision factor in selecting goods and services. In the process of checking the audio end section 8 types of defects found on the product DVD players. Damage that occurs due to several factors, including factors human, material factors, and factors machines. If the quality of a company is said to have good production systems with process control. Six Sigma method is a method that can be used for analysis of the defect rate to approach zero defect products. The procedures used for quality improvement towards the target that the concept of Six Sigma DMAIC. This study aims to apply Six Sigma methods in quality control by conducting case studies to improve product quality DVD player at the end of the audio process. The results obtained in this study is on the whole production process mengkasilkan DPMO value of 5487 with sigma quality level of 4.04 means that the product of one million DVD players there are 5487 units of product that does not fit in production. Keywords : Quality, Statistical Quality Control, Six Sigma